Chitosan/sodium tripolyphosphate nanoparticles as efficient vehicles for enhancing the cellular uptake of fish‐derived peptide. Issue 2 (14th November 2018) - Zhao, Yuanhui; Du, Wenwen; Wu, Haohao; Wu, Miaomiao; Liu, Zunying; Dong, Shiyuan
Abstract: Methodology to enhance the intestinal absorption of peptides is an important challenge due to their easily degradation and poor permeability across the intestinal epithelium. In this study, the fish‐derived peptide (DGDDGEAGKIG)‐loaded chitosan (CS) nanoparticles (CS/PEP‐NPs) were prepared and investigated in Caco‐2 monolayer model. The results indicated zeta potential of CS/PEP‐NPs increased with the increase in molecular weight of CS (10–50 kDa). Transmission electron microscopy images revealed the CS/PEP‐NPs were uniform spherical‐shaped nanoparticles with a diameter of 50–200 nm (150 kDa). Compared to other CS/PEP‐NPs, 150‐kDa CS/PEP‐NPs performed an outstanding apparent permeability coefficient (Papp, 2.29 × 10 −5  cm s −1 ) and cumulative amount of peptide (120 min, 2, 987 ng) in Caco‐2 cells. CS/PEP‐NPs could reduce the tight junction integrity of Caco‐2 cells and enhance the intracellular fluorescence intensities of fluorescein isothiocyanate‐labeled peptide. These findings suggest that chitosan nanoparticles are promising carriers to promote intestinal absorption of fish‐derived peptide via paracellular pathway mediated by tight junctions. Practical applications: Chitosans are promising carriers to promote intestinal absorption of fish‐derived peptide. The 150‐kDa CS/PEP‐NPs performed an outstanding apparent permeability coefficient (Papp, 2.29 × 10 −5  cm s −1 ) and cumulative amount of peptide (120 min, 2, 987 ng) in Caco‐2 cells. CS/PEP‐NPs could reduce the tight junction integrity of Caco‐2 cells and enhance the peptide uptake by paracellular pathway. Chitosan nanoparticles can be developed as vehicles for enhancing the cellular uptake of peptide in food industry.